The answer is Eight ninetieths
Pls mark as brainliest thx
Answer:
k(x) + g(x) = x² - 3x + 4
General Formulas and Concepts:
<u>Alg I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 3x - 7
g(x) = 2x² - 3x + 1
h(x) = 4x + 1
k(x) = -x² + 3
<u>Step 2: Find k(x) + g(x)</u>
- Substitute: k(x) + g(x) = -x² + 3 + 2x² - 3x + 1
- Combine like terms (x²): k(x) + g(x) = x² + 3 - 3x + 1
- Combine like terms (Z): k(x) + g(x) = x² - 3x + 4
Answer:
15 is the distance
Step-by-step explanation:
Answer: 249
Step-by-step explanation: 210+698-812+1453-1300
Answer:
<h2>A. 7</h2>
Step-by-step explanation:
Put z = 5 to the expression (10 + 25) ÷ z:
(10 + 25) ÷ 5 = 35 ÷ 5 = 7